Pengaruh Pemberian Bungkil Kelapa Sawit Segar (BKS) dan Fermentasi (BKSF) Terhadap Kualitas Fisik Telur Itik - Arif Pranata (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2017)
This research was conducted to utilize fresh and fermented palm kernel cake in the ducks diets on egg physical quality. One hundred and five laying ducks were randomly devided in to five diets treatments in three replications with seven laying ducks each the dietary treatments were K = control, was diet without palm kernel cake, BKS 10 and BKS 30 diets with addition 10 % and 30 % fresh palm kernel cake, BKSF 10 and BKSF 30 diets with addition 10 % and 30 % fermented palm kernel cake. The data collected were egg mass, shell thickness, Haugh Unit and yolk colour and will be analyzed by a one way classification of variance analysis (CRD), followed by testing the significant mean by Duncan’s New Multiple Range Test (DMRT). The results showed the egg mass, shell thickness, and HU had not significant different and egg mass were (64,74, 65,71, 67,22, 65,39, 63,52 g), shell thickness were (0,47, 0,49, 0,44, 0,48, 0,45 mm), Haught Unit were (86,81, 87,44, 90,94, 88,15, 88,08 %). Yolk colour had significant different between the treatment (9.31, 9,72, 9,81, 10,69, 10,74). It be concluded that the utilization 30% of fresh and fermented palm kernel cake in feed duck had not increase egg mass, shell tickness, and haugh unit, except on yolk colour. Key words :Fermentation, Egg Quality, Laying Duck, Palm kernel cake